Atherogenic Index of Plasma (AIP) a Tool to Assess Changes in Cardiovascular Disease Risk Post Laparoscopic Sleeve Gastrectomy - Eman Al Shawaf; Ebaa Al-Ozairi; Fahad Al-Asfar; Anwar Mohammad; Shaima Al-Beloushi; Sriraman Devarajan; Fahd Al-Mulla; Jehad Abubaker; Hossein Arefanian (Journal of Diabetes Research)
Predictive indices like the atherogenic index of plasma (AIP) have been developed to estimate the risk of cardiovascular disease (CVD). Metabolic surgery is the most effective treatment for a rapid improvement of morbid obesity and its comorbidities such as type 2 diabetes (T2D) and CVD. A decreased reoccurrence of CVD after metabolic surgery has been reported by several studies. However, studies utilizing predictive indices for CVD risk in CVD-free morbid-obese patients who undertook laparoscopic sleeve gastrectomy (LSG) are lacking. Here, we use AIP as a tool to evaluate the improvement in CVD risk post-LSG in morbid-obese people who had no history of CVD. Method. We compared baseline, 6- and 12-month post-LSG score of AIP, vascular age, circulating biochemical markers related to CVD in two groups of BMI and age-matched morbid-obese participants with and without T2D. Results. At baseline, people with T2D had significantly higher AIP both, with morbid obesity (0.23±0.06, p<0.001) and normal weight (0.022±0.05, p<0.001) compared to their BMI-matched without T2D group. People with morbid obesity had low AIP (−0.083±0.06). Vascular age was significantly higher in people with morbid obesity and T2D (65.8±3.7year, p<0.0001) compared to morbid obesity (37.9±2.6 year). After one year, AIP was significantly reduced compared to baseline score in people with morbid obesity with/without T2D, respectively (−0.135±0.07, p=0.003; and −0.36±0.04, p=0.0002). Conclusion. Our data illuminates AIP as a reliable predictive index for CVD risk in morbid-obese people who had no history of CVD. Moreover, AIP accurately distinguishes between morbid obesity with T2D and morbid obesity and showed a rapid and significant reduction in CVD risk after LSG in people who had no history of CVD. This is a ClinicalTrials.gov registered trial (Reference NCT03038373).